2020
DOI: 10.1002/adfm.202005776
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Enhancement for Highly Stable and Efficient Perovskite Solar Cells

Abstract: With a certified efficiency as high as 25.2%, perovskite has taken the crown as the highest efficiency thin film solar cell material. Unfortunately, serious instability issues must be resolved before perovskite solar cells (PSCs) are commercialized. Aided by theoretical calculation, an appropriate multifunctional molecule, 2,2‐difluoropropanediamide (DFPDA), is selected to ameliorate all the instability issues. Specifically, the carbonyl groups in DFPDA form chemical bonds with Pb2+ and passivate under‐coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
280
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 322 publications
(293 citation statements)
references
References 63 publications
12
280
0
1
Order By: Relevance
“…The incorporation of FEA in perovskite films changes the local bonding at the surface and boundaries. From the crystals’ results and previous reports, [ 22,33 ] the more F, the stronger the interaction with NH 2 and Pb. The most dramatic change is that the NH 2 surrounding an F site reorient toward the FEA via hydrogen bonds.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The incorporation of FEA in perovskite films changes the local bonding at the surface and boundaries. From the crystals’ results and previous reports, [ 22,33 ] the more F, the stronger the interaction with NH 2 and Pb. The most dramatic change is that the NH 2 surrounding an F site reorient toward the FEA via hydrogen bonds.…”
Section: Resultsmentioning
confidence: 61%
“…It is observed that the 1FEA has the largest recombination resistance, which is beneficial for suppressing photo‐generated charge recombination. [ 33 ] The space‐charge‐limited current (SCLC) measurements for the control, 1FEA, 2FEA, and 3FEA devices are conducted, and the results are shown in Figure 2e–h. The structure fluorine‐doped tin oxide (FTO)/TiO 2 /perovskite/PEAI/PCBM/Ag is adopted for these measurements.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, many other kinds of passivation materials have also been reported with excellent photovoltaic performance and superior stability, such as organic molecules, polymers, ionic liquids, and Lewis acids and bases. [ 33–44 ]…”
Section: Introductionmentioning
confidence: 99%
“…Recently, fluorination has been found as a facile and efficient way to improve the device performance, [8a–c] such as in organic solar cells and lead hybrid PSCs [5,8b] . When a hydrogen atom on the benzene ring is replaced by other atoms or groups, the distribution of the electron cloud on the benzene ring is changed, and thus the nucleophilic property of the benzene ring will be altered [9] .…”
Section: Introductionmentioning
confidence: 99%